Universal bispecific antibody for targeting tumor cells for destruction by cytotoxic T cells. - Gilliland, L; Clark, MR; Waldmann, H (1988)
Previous studies have demonstrated that bispecific hybrid antibodies produced by cell-cell fusion or chemically conjugated heteroaggregates can direct cytotoxic T lymphocytes to kill target cells for which they have no intrinsic specificity, a phenomenon we call effector cell retargeting (ECR). These studies used bispecific reagents with one specificity directed to CD3 or Ti on the effector cell and the other directed to a target cell antigen. To avoid the need to create different hybrid hybridomas for each target antigen we have developed a universal means to elicit ECR through the use of an antiglobulin step. We have constructed a bispecific hybrid antibody with dual specificity for CD3 and a rat immunoglobulin light chain allotype. This bispecific antibody could mediate ECR to a range of target cells, each coated with distinct surface-binding rat monoclonal antibodies. A particular advantage of targeting to surface-bound monoclonal antibodies is that all other available effector systems may also attack the same antibody-coated target cell.